2022
DOI: 10.1177/21676968221097167
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Attachment to Parents and Peers and Relations With Mental Health During the COVID-19 Pandemic

Abstract: Using a longitudinal design, we examined changes in parent and peer attachment among college students, and their predictive and protective roles in relation to mental health problems during the COVID-19 pandemic. College students ( N = 106) rated their parent and peer attachment, and self-reported anxiety, loneliness, and depressive symptoms 1 year before and during the pandemic. Participants also rated the impact of COVID-19 related stressors (CRS). Results demonstrate significant increases in loneliness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…Indeed, we found that the direct effects of attachment to peers on levels of alexithymia, peritraumatic distress, and IA were all significant, as were the indirect paths via the simple mediation of both alexithymia and peritraumatic distress and the multiple serial mediation of alexithymia and peritraumatic distress. These findings are in line with previous studies evidencing that the insecurity of attachment to peers may predispose young adults to higher difficulties in identifying and describing feelings [ 141 ], psychopathological symptoms [ 142 ], and internet-related addiction [ 133 ]. Moreover, we found greater effect sizes of the effects of attachment to peers on IA compared to those directly and/or indirectly exerted by the attachment to mothers and to fathers.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, we found that the direct effects of attachment to peers on levels of alexithymia, peritraumatic distress, and IA were all significant, as were the indirect paths via the simple mediation of both alexithymia and peritraumatic distress and the multiple serial mediation of alexithymia and peritraumatic distress. These findings are in line with previous studies evidencing that the insecurity of attachment to peers may predispose young adults to higher difficulties in identifying and describing feelings [ 141 ], psychopathological symptoms [ 142 ], and internet-related addiction [ 133 ]. Moreover, we found greater effect sizes of the effects of attachment to peers on IA compared to those directly and/or indirectly exerted by the attachment to mothers and to fathers.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our findings uncovered various aspects of what it feels like to be lonely amid COVID-19. Although closer friendships seem to remain intact in the pandemic (72), it is associated with less general peer-topeer contact (73) and worse recognition of one's own and others' emotions (74), which can lead to more distress and loneliness (73). When looking back at the possible evolutionary functions of loneliness, solidarity and spending time with a peer group help increase social skills for battling loneliness, which in turn lessens their risk for mortality (43).…”
Section: Discussionmentioning
confidence: 99%
“…While the current study was conducted prior to the advent of COVID-19 in 2015, its emphasis on attachment and identity for university adjustment aligns with more recent findings in the context of the pandemic. During the COVID-19 pandemic, [ 97 ] investigated changes in parent and peer attachment and the associated adjustment challenges among college students in the United States. They discovered that students reported lower attachment security, which was associated with greater adjustment difficulties.…”
Section: Discussionmentioning
confidence: 99%